1969
DOI: 10.2337/diab.18.12.834
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Human Plasma Insulin Sephadex Fractions

Abstract: Fifty-nine samples taken from lean and obese healthy subjects and from patients with diabetes mellitus, myotonic dystrophy, and islet cell adenoma after the administration of oral or intravenous glucose or other insulin secretogogues were fractionated on Sephadex G-50 columns. Eluates corresponding to zones of elutions of porcine pro insulin ("big insulin") and Regular insulin were assayed for insulin by radioimmunoassay using crystalline human insulin as standard and porcine insulin-I-125 as tracer. In four s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

1971
1971
1984
1984

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(22 citation statements)
references
References 7 publications
4
18
0
Order By: Relevance
“…8). This finding is compatible with the known effects of glucose in stimulating both the synthesis and release of insulin (3,22 (23). In most of their patients the per cent proinsulin-like component was higher in the 2nd and 3rd hr after oral glucose than at 30 min after the glucose load.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…8). This finding is compatible with the known effects of glucose in stimulating both the synthesis and release of insulin (3,22 (23). In most of their patients the per cent proinsulin-like component was higher in the 2nd and 3rd hr after oral glucose than at 30 min after the glucose load.…”
Section: Resultssupporting
confidence: 78%
“…ponent is higher in islet-cell tumor patients than in most other patients studied, comprising from 26 to 79% of the total insulin. In individual cases a range of from 3 to 67% of basal and stimulated proinsulin-like component has been reported (1,15,16,(23)(24)(25).…”
Section: Resultsmentioning
confidence: 99%
“…The proinsulin content of extracted pancreas is less than 7% of the immunoreactive insulin level (26)(27)(28)(29)(30)(31)(32), while basal values in peripheral blood are higher, comprising approximately 20% of total IRI (7,(33)(34)(35)(36). Although it has been suggested that the higher circulating proinsulin content indicates preferential release of newly formed granules, which contain a higher proportion of proinsulin, our data on portal vein blood indicate that the ratio of proinsulin to insulin being secreted is similar to that present in the pancreas.…”
Section: Discussionmentioning
confidence: 41%
“…Proinsulin, the single-chain polypeptide precursor of insulin, has been identified in human (1)(2)(3)(4)(5)(6), bovine (7,8), transaminase was assayed (18) in the initial and final perfusate sample from each experiment. The values were below 10 IU and did not increase significantly in the latter samples.…”
Section: Introductionmentioning
confidence: 99%